A new 5-input majority gate without adjacent inputs crosstalk effect in QCA technology - Ali Majeed; Esam Alkaldy; Mohd Shamian Zainal; Danial Md Nor (Institute of Advanced Engineering and Science, 2019)
Transistor-based CMOS technology has many drawbacks such as power consumption and cannot continue in following the scaling of Moore's law and system-on-a-chip in near future. These drawbacks lead the researchers to think about an alternative technology. Quantum-dot Cellular Automata (QCA) is a new nanoscale technology can implement the logical functionality by controlling the position of the electron. The basic building blocks for QCA circuit are majority gate and inverter. where AND and OR gate can be implemented using Majority gate by setting one of the inputs to